Chronic Form of Dematophilosis Treatment Response With Long‐Acting Oxytetracycline in Cattle: Case Report - Negessa Diriba Hordofa; Teshale Sori; Bethel Befekadu (Veterinary Medicine and Science)
ABSTRACT Dermatophilosis is dermatitis with acute, subacute and chronic courses which is usually exudative and rarely proliferative and can affect cattle, sheep, goats and horses and sometimes in humans. A 5‐year‐old local breed bull was presented to Professor Feseha Gebreab Memorial Veterinary Teaching Hospital of the College of Veterinary Medicine and Agriculture, Addis Ababa University, with main complaints of dry skin lesions which started before one year of presentation. Upon clinical examination, the bull was in good body condition, and there was a dry scabby skin lesion on its dorsum and ventral parts. Impression smear was made from the beneath scabs, and staining was done by Giemsa. The examined smear revealed typical railroad stack arrangements of organisms by the staining. The skin lesion was scrubbed with 10% sodium chloride solution; lesions were removed and disinfected with cetrimide 3% and chlorhexidine 0.3% (Cavlon) solution. Iodine 2% was applied topically for 5 successive days. The bull was treated with seven doses of long‐acting oxytetracycline (20%) deep intramuscular injection at a dose of 20 mg/kg for 7 days. After a treatment course of 5 weeks, the removed crusts re‐emerged again and the disease was not responsive to the given drug. The severity of the lesion might be the cause of disease relapse, and individual animal factors could have influenced the treatment's resistive response and it need further study to determine whether oxytetracycline is beneficial in treating chronic dermatophilosis.